1913
DOI: 10.1055/s-0028-1128019
|View full text |Cite
|
Sign up to set email alerts
|

Die Blutzirkulation in atmenden und atelektatischen Lungen1)

Abstract: In einer der Sitsungen des letzten Jahres konnte ich berichten über systematische 1Jnteruchungen der Blutgase bei den verschiedenen Affektionen der Atmungsorgane, insbesondere beim offenen und geschlossenen Pneumothorax. Diese aus anderen Gründen vorgenommenen Untersuchungen wiesen nun darauf hin, daß die Durchblutung der erkrankten Lungenpartien hinter der atmender, normaler Lungenabschnitte zurücksteht; eine Beobachtung, die dann durch die Blutgasanalysen von Morawitz und Hess bestätigt wurde. Um nun aber ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1917
1917
1968
1968

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…During the early part of the century, when artificial pneumothorax was widely used as a therapeutic measure, there was considerable interest in its physiological effects. Studies in animals (Bruns, 1913;Adams and Morris, 1921 ;Weiss, 1926;and Moore, 1931) showed that shortly after induction of a pneumothorax there was a considerable fall in arterial oxygen saturation which returned to normal a few hours later. This, in the absence of a change in total ventilation, was thought to be due to an initial shunt of blood through the collapsed lung which gradually lessened due to pulmonary vasoconstriction.…”
mentioning
confidence: 99%
“…During the early part of the century, when artificial pneumothorax was widely used as a therapeutic measure, there was considerable interest in its physiological effects. Studies in animals (Bruns, 1913;Adams and Morris, 1921 ;Weiss, 1926;and Moore, 1931) showed that shortly after induction of a pneumothorax there was a considerable fall in arterial oxygen saturation which returned to normal a few hours later. This, in the absence of a change in total ventilation, was thought to be due to an initial shunt of blood through the collapsed lung which gradually lessened due to pulmonary vasoconstriction.…”
mentioning
confidence: 99%